Green Synthesis Nanopartikel Seng Oksida (Zno) dengan Menggunakan Ekstrak Daun Kakao Sebagai Capping Agent: Green Synthesis Nanopartikel Seng Oksida (Zno) dengan Menggunakan Ekstrak Daun Kakao Sebagai Capping Agent - Repiani, Repiani; Handani, Sri; Puryanti, Dwi (Universitas Andalas, 2025)
A study was conducted to investigate the effect of varying concentrations of cocoa leaf extract on ZnO nanoparticles as a capping agent. The concentrations of cocoa leaf extract were varied at 0%, 2%, 4%, 6%, and 8%, and tested to observe their effects on crystal size, optical properties, and morphology of the ZnO nanoparticles. The ZnO nanoparticles were synthesized using the sol-gel method with cocoa leaf extract. The success of the synthesis was indicated by the similarity of the peaks from the synthesized compounds to the standard ZnO peaks in the X-Ray Diffraction (XRD) analysis. The resulting crystal structure was hexagonal wurtzite, with crystal sizes for each extract concentration of 54.393 nm, 54.01 nm, 54.39 nm, 45.61 nm, and 38.45 nm, respectively. UV-Vis spectrometer analysis showed that the ZnO nanoparticles were relatively stable at wavelengths between 228 nm and 366 nm, with bandgap energy values for each extract concentration being 3.11 eV, 3.13 eV, 3.11 eV, 3.14 eV, and 3.15 eV, respectively. The UV-Vis results indicated that the bandgap energy increased with increasing concentrations of cocoa leaf extract, while the crystal size decreased, which was consistent with the XRD results. Scanning electron microscope (SEM) analysis showed that ZnO nanoparticles synthesized with 4% cocoa leaf extract predominantly exhibited a spherical shape, with an average size of 45 nm.